Stroke as the First Manifestation of Atrial Fibrillation - Jaakkola J; Mustonen P; Kiviniemi T; Hartikainen JEK; Palomaki A; Hartikainen P; Nuotio I; Ylitalo A; Airaksinen KEJ (PUBLIC LIBRARY SCIENCE, 2022)
Atrial fibrillation may remain undiagnosed until an ischemic stroke occurs. In this retrospective cohort study we assessed the prevalence of ischemic stroke or transient ischemic attack as the first manifestation of atrial fibrillation in 3,623 patients treated for their first ever stroke or transient ischemic attack during 2003-2012. Two groups were formed: patients with a history of atrial fibrillation and patients with new atrial fibrillation diagnosed during hospitalization for stroke or transient ischemic attack. A control group of 781 patients with intracranial hemorrhage was compiled similarly to explore causality between new atrial fibrillation and stroke. The median age of the patients was 78.3 [13.0] years and 2,009 (55.5%) were women. New atrial fibrillation was diagnosed in 753 (20.8%) patients with stroke or transient ischemic attack, compared to 15 (1.9%) with intracranial hemorrhage. Younger age and no history of coronary artery disease or other vascular diseases, heart failure, or hypertension were the independent predictors of new atrial fibrillation detected concomitantly with an ischemic event. Thus, ischemic stroke was the first clinical manifestation of atrial fibrillation in 37% of younger (<75 years) patients with no history of cardiovascular diseases. In conclusion, atrial fibrillation is too often diagnosed only after an ischemic stroke has occurred, especially in middle-aged healthy individuals. New atrial fibrillation seems to be predominantly the cause of the ischemic stroke and not triggered by the acute cerebrovascular event.